Pengembangan Media Pembelajaran MOTIF (Monopoli Edukatif Fikih) pada Mata Pelajaran Fikih di MA al-Bairuny - Nadia Falasifah; Khoirun Nisa'; Chusnul Chotimah (ANWARUL, 2026)
The low learning interest of students, influenced by the dominance of lecture methods and conventional learning, became the basis for developing MOTIF, or Educational Fiqh Monopoly, learning media in the Fiqh subject at MA Al-Bairuny. This study aims to produce interactive learning media based on an educational game that can improve students’ engagement and understanding in the Fiqh learning process. This study used the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, planning, development, implementation, and evaluation. The research subjects consisted of Grade X students at MA Al-Bairuny. Data were collected through observation, interviews, documentation, and questionnaire distribution to validators and students. The validation results showed that the MOTIF media obtained a very feasible category based on material expert assessment and a very attractive category based on media expert assessment, indicating that it can be used in learning activities. In addition, the field trial results showed positive student responses to the use of MOTIF media because it was considered capable of creating a more engaging, interactive, and enjoyable learning atmosphere. The conclusion of this study affirms that the development of MOTIF learning media can serve as an innovative alternative in Fiqh learning. The implications of this study indicate that educational game media can encourage students to be more active, motivated, and enthusiastic in understanding Fiqh learning material.